Commercialization Model Design and Presentation of Proposed Algorithm of Knowledge Commercialization for the Higher Education - Tahereh Salamati; Ehsan Vaezi; Mehdi Memarpour; Ali Rajabzadeh (بازیابی دانش و نظام‌های معنایی, 2016)
The growing importance of commercialization and special attention paid to this topic of discussion at global university level makes the study on this matter justifiable. On basis of this assumption the commercialization which has been named as the connection link between universities and industries or (market) must become operational in the frame work of a practical and effective model.The study and evaluation of the practical models widely used in the world reveals that, the environmental factors play an important role in the process of commercialization. Therefore, the model to be designed and chosen must be indigenous and suitable for domestic conditions of the country. In other words, it should applicable to and practical for the use in Iranian organizations. In this study, it has been tried to present a comprehensive model. By designing a comprehensive model in this connection, this significant matter has been fulfilled in this research. Also, in line with the nature of the design of this model the major roles of the fundamental researches has been examined and an algorithm suitable for the country research environment which can oversee the innovative activities of commercial firms (with special emphasis on academic innovation) has been prepared which is more appropriate for the ideas coming out from the heart of university researches that is most proper for the use in academic firms and institutes and also to can be used in incubators and development centers. Of course, this algorithm and procedure with slight changes can also have a general application.